كێشە كۆمەڵایەتیەكانی خێزان توێژینەوەیەكی مەیدانیە لە پارێزگاى هەڵەبجە - محمود, بهاالدین فرج (Sulaimani Journal for Humanities, 2023)
It is certain that misfortunes and problems arise in family life, and these problems if not dealt with scientifically and not treated, lead to the dissolution and distributed in a field manner, and the research group consists of (104) people who filled out the questionnaires in this way the data was collected, the data of the study were collected between November 2022- January 2023.The study concluded that family problems are at unhealthy levels, and there are common social reasons for these problems, such as the presence of misfortunes in the lives of families in the study community.